2015
DOI: 10.1186/s12940-015-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

The associations between daily spring pollen counts, over-the-counter allergy medication sales, and asthma syndrome emergency department visits in New York City, 2002-2012

Abstract: BackgroundMany types of tree pollen trigger seasonal allergic illness, but their population-level impacts on allergy and asthma morbidity are not well established, likely due to the paucity of long records of daily pollen data that allow analysis of multi-day effects. Our objective in this study was therefore to determine the impacts of individual spring tree pollen types on over-the-counter allergy medication sales and asthma emergency department (ED) visits.MethodsNine clinically-relevant spring tree pollen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
3
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 32 publications
12
110
3
3
Order By: Relevance
“…Depending on the allergen source (e.g., trees, grass, weeds), the pollen counts in the air are generally highest during mid-spring to early summer when 75% of environmental pollen exposure occurs. The link between spring peaks in highly allergenic trees (such as oak) and allergic rhinitis in spring is confirmed by multiple lines of evidence, including over-the-counter allergy medication purchases [42]. In temperate regions, grass pollen is principally released during the summer months.…”
Section: Aeroallergens: Sources and Seasonalitymentioning
confidence: 99%
“…Depending on the allergen source (e.g., trees, grass, weeds), the pollen counts in the air are generally highest during mid-spring to early summer when 75% of environmental pollen exposure occurs. The link between spring peaks in highly allergenic trees (such as oak) and allergic rhinitis in spring is confirmed by multiple lines of evidence, including over-the-counter allergy medication purchases [42]. In temperate regions, grass pollen is principally released during the summer months.…”
Section: Aeroallergens: Sources and Seasonalitymentioning
confidence: 99%
“…Short-term increases in aeroallergens have been associated with allergic and asthma exacerbations in the general population, 16 and among children. 7,8 In addition, one study found that exposure to high levels of pollen during late pregnancy was associated with an increased risk of hospitalization for asthma within the first year of life of children.…”
mentioning
confidence: 99%
“…Details of the experimental technique used for sample collection and measurement of various genera of pollen are described elsewhere [29, 30]. We log-transformed daily concentrations (grains per cubic meter) for tree, weed, and total pollen, and created an indicator variable for outdoor pollen if daily concentrations exceeded the 5 th percentile of the concentration distribution.…”
Section: Methodsmentioning
confidence: 99%